2021
DOI: 10.1097/md.0000000000025735
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of depression-related factors among middle-aged residents in Japan, an Eastern culture

Abstract: There is a need to comprehensively identify depression-related factors, including individual and socioeconomic factors, in each country or cultural area, to consider effective measures to address depression within communities. However, there are not enough studies on middle-aged residents in Japan or other Eastern countries to currently achieve this. Thus, the aim of this study was to comprehensively identify factors related to depression in middle-aged residents in Japan, an Eastern country. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In a previous study, it was found that higher workplace social capital was related to better mental health of employees [15] . Furthermore, workplace recreation or having hobbies could influence mental health [16,17] . Thus, fostering social capital through workplace recreation is an effective mental health measure for SMEs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous study, it was found that higher workplace social capital was related to better mental health of employees [15] . Furthermore, workplace recreation or having hobbies could influence mental health [16,17] . Thus, fostering social capital through workplace recreation is an effective mental health measure for SMEs.…”
Section: Discussionmentioning
confidence: 94%
“…[15] Furthermore, workplace recreation or having hobbies could influence mental health. [16,17] Thus, fostering social capital through workplace recreation is an effective mental health measure for SMEs. However, employees who do not want to have intimate relationships at work are currently increasing.…”
Section: Awareness Of Mental Health Promotion Measures For Employees ...mentioning
confidence: 99%
“…It is a heavy burden for teachers to balance child protection and disaster evacuation management. Continued stress leads to high levels of burnout and turnover [13,14]. Post-disaster mental health measures are not the only way to prevent burnout.…”
Section: Introductionmentioning
confidence: 99%